Study on the Properties and Structure of Nano-TiO2 Modified Silk Fibroin Films (Journal of Fiber Bioengineering and Informatics, 2018)
A kind of regenerated Silk Fibroin (SF), nano-blended membrane, was made using an ionic liquid as asolvent. The membranes were characterized by SEM, XRD, FTIR, TG. The SEM showed that moreagglomerations were observed with the increase of blended nano-TiO_2 (TD). XRD and FTIR verifiedthat nano-TD made conformational changes in SF membrane and the conformation changes from randomcoil or Silk I into Silk II with the increase of nano TD. The TG analysis showed that pure silk fibroinmembrane and nano TD membranes had only one apparent thermal transition region, at about 300 °C.Based on the mechanical performance test of SF membranes, tensile strength obviously increased whenthe amount of nano TD increased, which indicated that the mechanical strength improved with theaddition of certain amount of nano TD.